Analysis and interpretation of organizational silence behavior of male nurses from the perspective of phenomenology - Mengjing Yan; Zhenyin Shi; Aihua Zhou; Shuqin Zeng (BMC Nursing)
Abstract Background Male nurses play an important role in the nursing industry, but organizational silence is prevalent, leading to high turnover rates, a young and unstable workforce, and hindering the development of the nursing profession. This study aims to analyze the underlying causes of organizational silence among male nurses and provide empirical evidence for managers to stabilize the male nursing workforce and tap into their value. Method Using WeChat as an online communication platform, we conducted semi-structured interviews with 16 male nurses from four tertiary hospitals in Guangdong Province (southern China), Hunan Province (central China), Guizhou Province (southwestern China), and Jiangxi Province (southeastern China) using an interpretive phenomenological research method. The data were analyzed using Colaizzi’s phenomenological analysis method. Results Male nurses’ experiences of organizational silence were distilled into three themes: the influence of leadership on speaking up, low social acceptance, and subjective influence. Conclusion This study found that organizational silence among male nurses is widespread and severe, influenced by various factors such as organizational atmosphere, policy systems, and social recognition. Nursing managers should optimize management strategies, improve communication, enhance male nurses’ professional identity, and establish reasonable training pathways to enhance their professional and academic capabilities, thereby gaining social recognition, stabilizing the nursing workforce, and promoting the diversification and high-quality development of the nursing profession.